PEMBERDAYAAN KELOMPOK DASAWISMA UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI KELUARGA DI DESA JAWAPOGO, KECAMATAN MAUPONGGO, KABUPATEN NAGEKEO: - Skolastika Sania Parihi; Veronika Ruba Pena; Eusabius Separera Niron; Bruno Rey Sonby Pantola (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
Jawapogo Village, Mauponggo District, Nagekeo Regency has faced two main problems. The problems faced are lack of skills and inability to access optimal economic resources, especially in terms of utilizing local potential such as candlenut fruit. The purpose of this community service is to encourage Dasawisma groups to improve family financial welfare. Observation, socialization, discussion, and skills training for Dasawisma mothers are all techniques used. This activity is carried out in four main stages, namely starting with preparation and observation to determine community needs, then Dasawisma mothers also learn about the importance of managing economic resources and talking about existing problems. Skills training concentrates on making candlenut oil and other value-added products from candlenut fruit. The results of the program show that the knowledge and skills of Dasawisma mothers on how to process candlenuts have increased. This has a positive impact on family income and community economic independence. Therefore, this empowerment program not only improves the economy but also helps women become part of village decision-making and creates new sustainable business opportunities.